Long-Term Outcomes of Left Atrial Appendage Electrical Isolation in Patients With Nonparoxysmal Atrial Fibrillation: A Propensity Score-Matched Analysis. (November 2020) - Romero, Jorge; Di Biase, Luigi; Mohanty, Sanghamitra; Trivedi, Chintan; Patel, Kavisha; Parides, Michael; Alviz, Isabella; Diaz, Juan C.; Natale, Veronica; Sanchez, Javier; Della Rocca, Domenico G.; Yang, Ruike; et al.
Abstract : Background: Left atrial appendage electrical isolation (LAAEI) has been proposed for the treatment of nonparoxysmal atrial fibrillation (AF). The long-term clinical outcomes of this approach remain unclear. The objective of our study was to investigate the incremental benefit and safety of LAAEI in patients undergoing catheter ablation for nonparoxysmal AF. Methods: Propensity score-matched analysis was performed using a prospective registry database from 2010 to 2014. All patients in the LAAEI group were matched based on baseline characteristics, echocardiographic parameters, and procedural ablation techniques. Results: We identified 1842 patients who underwent catheter ablation for nonparoxysmal AF. Propensity score matching yielded 1092 patients, 546 patients with LAAEI, and 546 patients without LAAEI. At 5-year follow-up, overall freedom from all-atrial arrhythmia recurrence, off-antiarrhythmic drugs, in patients who underwent LAAEI was 68.9% versus 50.2% in those who underwent standard ablation alone ( P <0.001). Acute complication rates were similar between groups (LAAEI 1.3% versus non-LAAEI 0.73%, P =0.36). At 5-year follow-up, 382 (70%) patients in the LAAEI group remained on oral anticoagulation versus 217 (39.7%) in the non-LAAEI group. At 5-year follow-up, thromboembolic events occurred in 15/546 (2.75%) in the LAAEI group and 4/546 (0.73%) in the non-LAAEI group ( P =0.01). No thromboembolic events occurred in either group on-oral anticoagulation. In patients who were off-oral anticoagulation, at 5-year follow-up, thromboembolic events occurred in 15/164 (9.1%) in the LAAEI group and 4/329 (1.2%) in the non-LAAEI group ( P <0.001). Conclusions: At 5-year follow-up, LAAEI was associated with significantly higher freedom from all-atrial arrhythmia recurrence in patients with persistent and long-standing persistent AF without increasing acute procedural complication rate. In patients off-oral anticoagulation, there appears to be a higher risk of thromboembolic events in the LAAEI group.